Application and comparison of level control strategies in the slug flow problem using a mathematical model of the process - doi: 10.4025/actascitechnol.v34i4.13020 - Sausen, Airam; Sausen, Paulo Sergio; Reimbold, Manuel; Campos, Mauricio de (Acta Scientiarum. Technology, 2012)
This paper presents the application of the error-squared level control strategy Proportional Integral (PI) in the slug flow problem in oil production industry. For this purpose the dynamic model has been used for a pipeline-separator under slug flow with five Ordinary Differential Equations (ODEs), coupled, non-linear. The application of the error-squared level control strategy PI is performed through the methodology by bands, whose objective is to damp the oscillatory flow rate of the load that occur in production separators for equipment downstream of the process. This strategy is compared with the level control strategy PI conventional, widely used in industrial processes; and with the level control strategy PI, also, in the methodology by bands. Simulation results showed that the error-squared level control strategy PI in the methodology by bands, presented better results when compared with the level control strategy PI conventional, because reduced flow fluctuations caused by slug flow; and with the level control strategy PI in the methodology by bands, it probably happened because the first has highly respected the defined bands.